Effect of perturbations on plasmon dispersion in monovalent metals - Pandey N.L.; Singh R.N. (My University, 2025)
Dispersion characteristics of plasmon in degenerate electron gas in monovalent metals have been studied. Accounting for the perturbations set by long range forces and the effect of short range interactions, it is shown that at a critical wave number the oscillations are inhibited. © 1975.